Effect of Thermal Treatment on Some Physical and Mechanical Properties of Cermet Coating by Flame Spraying Technology (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this research, thermal flame spraying technology was used for the purpose of producing a ceramic composite material produced from a mixture of ceramic material Al2O3, 25% and 50% with Ni-Al bonding material by 75% and 50% respectively, Coating through tests. The paint was made of graphite after it was tarnished by teething method. The spraying distance was 12 cm. The thermal treatment of the coated samples was at 1000 ولفت and for a period of two hours only. Through the tests of porosity, hardness and x-ray resistance, it was found that the best ratio of ceramic coating was in the ratio (50% alumina) with (50% of the bonding material). Where the best porosity was about 50% of the alumina and of the bond material as it reached 10.52%, the best hardness was also at 50% of the alumina and 50% of the bonding material as it reached 47.48Hv, the thermal treatment helped reduce the porosity to 7.44% and increased the hardness to 56.22Hv at the rate of 50% of the alumina and 50% of the bonding material, Finally the thermal treatment at (1000 ℃ ) and for two hours helped improve the crystalline uniformity at the angles of diffraction of defects.